Sistem Informasi Agenda, Arsip, dan Persuratan Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Hulu Sungai Tengah - Rahman, Muhammad Hafif; Santosa, Tri Budi; Hasanah, Mahmudatun (Politeknik Harapan Bangsa Surakarta, 2024)
The Regional Development Planning Agency (Bappeda) of Hulu Sungai Tengah Regency has a strategic role in planning and coordinating regional development. However, the management of agendas, archives, and correspondence is still done manually, which is prone to data loss, physical damage, and difficulty in finding information. This study aims to design an integrated information system that can manage agendas, archives, and correspondence efficiently and effectively. Using the Waterfall method in the System Development Life Cycle (SDLC), this system is able to increase productivity, accelerate access to information, and ensure data security and reliability. The results of this study are in the form of an information system that helps Bappeda in managing its tasks better, supporting the improvement of public services and the efficiency of the agency’s work. The implementation of this system includes agenda management, digital archiving, and management of incoming and outgoing letters, with ongoing evaluation and maintenance to ensure optimal performance.